Experimental determination of the adhesive characteristics of the “elementary fiber-epoxy matrix” system - Borodulin A. S.; Nelyub V. A.; Malysheva G. V.; Bertaeva A. A. (E3S Web of Conferences, 2023)
The paper considers the method of testing the elementary fiber-polymer matrix system. Results of determining the following adhesive characteristics are provided: apparent and local adhesive strength, start and end in the adhesive destruction of the fiber-matrix joint under study. Basalt fiber and epoxy matrix based on the epoxy resin and amine hardener are considered as the study objects. Influence of the samples geometric characteristics on their adhesive characteristics is established. The paper shows that at the depth of the elementary fiber emersion in the polymer matrix equal to 200 µm, the scatter of all determined adhesive characteristics is significantly reduced.